The trend and interest in sports cycling during the Covid-19 pandemic - Muhad Fatoni; Gatot Jariono; Subroto Subroto; Chandra Triadi (MEDIKORA, 2021)
The requirement for healthy breathing and maintaining body immunity defense is getting higher with the pandemic, mindfulness of the importance point of maintaining health and body immunity has become a new mindset approach in society. One of the efforts and hard works considered effective by the society to achieve realize in good physical nature and fit condition is by exercising. One of the sport that has many benefits is cycling. The perseverance of this study was to analyze trend and interest in society cycling during the pandemic. This research is quantitative descriptive. The research subjects were taken using purposive random sampling technique. The totally subjects studied in this study research were 130 people, which were divided into four groups (genres) of bicycles, namely BMX, Roadbike, Mountain Bike and Trial. In this research focuses in collected data. Data were collected using cross-sectional surveys using a Likert scale. The results of this research study are that there are 65 samples in the high category and get a percentage value of 50.00%, 63 samples in the medium category get a percentage value of 48.46%, and 2 samples in the less category get a percentage value of 1.54. %. Meanwhile, of the three types of bicycle genres that have the highest trend are road bikes with 62 respondents, then mountain bikes with 44 respondents, BMX and Trial with 12 respondents each. The conclusion of this study is that road bikes are the most trending genre among the public and the public interest in cycling during the Covid-19 pandemic is in the high category. TREN DAN MINAT OLAHRAGA BERSEPEDA MASYARAKAT PADA MASA PANDEMI COVID-19  AbstrakTuntutan untuk hidup sehat dan menjaga imunitas tubuh semakin tinggi dengan adanya pandemi, kesadaran tentang pentingnya menjaga kesehatan dan imunitas tubuh menjadi mindset baru dalam masyarakat. Salah satu upaya yang dianggap efektif oleh masyarakat untuk mencapai kondisi sehat dan bugar adalah dengan berolahraga. Salah satu olahraga yang memiliki banyak manfaat adalah olahraga bersepeda. Tujuan penelitian ini adalah untuk menganalisis tren dan minat olahraga bersepeda masyarakat pada masa pandemi. Penelitian ini merupakan penelitian deskriptif kuantitatif. Subjek penelitian diambil menggunakan teknik purpossive random sampling. Total subjek yang diteliti dalam penelitian ini berjumlah 130 orang, yang terbagi menjadi empat kelompok (genre) sepeda, yaitu BMX, Roadbike, Mountain Bike dan Trial. Pengambilan data dilakukan dengan memakai metode cross-sectional surveys menggunakan skala Likert. Hasil dari penelitian ini adalah ada 65 sampel memiliki minat yang tinggi dalam olahraga sepeda, dan dengan nilai presentase sebesar 50,00%, 63 sampel memiliki minat yang sedang dalam olahraga bersepeda, dengan nilai presentase sebesar 48,46%, dan 2 sampel dalam kategori minat rendah, dengan nilai presentase sebesar 1,54%. Sementara itu dari ketiga jenis genre sepeda yang memiliki tren paling tinggi adalah roadbike dengan 62 responden, kemudian mountain bike dengan 44 responden, BMX dan Trial dengan masing-masing 12 responden. Kesimpulan dari penelitian ini adalah bahwa sepeda roadbike menjadi genre paling tren di kalangan masyarakat dan minat olahraga bersepeda masyarakat pada masa pandemi covid-19 dalam kategori tinggi.